Applications in Clinical Administration Medical Record Service Health GPIB PAULUS MENTENG Using Visual Basic 6.0 - KLAUDA JUNIASA DAMAILAWASTU (Jurnal Sistem Informasi, 2009)
Currently a very rapid development of computer science, the application is already widespread  across the homeland Indonesia.Hal due speed and completeness in  data processing, accuracy and data processing plays a very important. So with this the author tries to discuss about the system  related computerized rekammedis on Health Services Clinic  GPIB PULUS MENTENG. Rekammedis recording activity can be seen from the input data of patients, inputting data doctor, inputting rekammedis patients, patient data searches to  with the printing of data report the doctor and patient data using Microsoft Visual Basic 6.0.